Combining motor imagery practice with physical practice optimizes the improvement in peak force control during thoracic spinal manipulation. - Dubant, Constance; Meugnot, Aurore (Journal of the Canadian Chiropractic Association, 2024)
Spinal manipulation learning requires intensive practice, which can cause injuries in students. Motor imagery (MI) paired with physical practice (PP) appears to be a suitable means to reduce the number of physical repetitions without decreasing skill outcomes. This study examines whether a session of MI paired with PP leads to a similar improvement in the ability to precisely produce peak forces during a thoracic manipulation as PP alone. Chiropractic students participated in a thoracic manipulation training program for five weeks. They were randomised in two groups: the MI+PP group performed sessions combining physical and mental repetitions with 1/3 fewer PP sessions, while the PP group performed only PP. Thoracic manipulation performance was assessed in pre and post-tests, consisting of thoracic manipulations at three different strength targets. Absolute error (AE), corresponding to the difference between the force required and the force applied by the student, was recorded for each trial. The main result revealed that AE was significantly lower in post-test than in pre-test for both groups. Despite fewer physical repetitions, the MI+PP participants showed as much improvement as the PP participants. This result supports the use of MI combined with PP to optimise the benefits of physical repetitions on thoracic manipulation learning.